Cellulose nanofiber thin-films as transparent and durable flexible substrates for electronic devices. (1st January 2021) - Pakharenko, Viktoriya; Sameni, Javad; Konar, Samir; Pervaiz, Muhammad; Yang, Weimin; Tjong, Jimi; Oksman, Kristiina; Sain, Mohini
Abstract: This work reports for the first time an exceptionally high thermal stability of cellulosic nanofibers films at 190 °C after a 5 h exposure, a threshold required for their design and manufacturing in flexible electronic devices. A long-term durability validation of a flexible cellulose nanofiber over a period of 10 years exposure under ambient condition validated their life-span over a long period of operating condition. Arresting quinoid oxidative reactions pathways and thermal degradation of lignin or lignin-less cellulose are demonstrated to be two fundamental routes to enhance thermal processing of cellulose nanofiber substrates and to achieve long service life of energy devices made from them. One of the main highlights of this work is the first time validation of a long operating service life for a light-emitting device made from a cellulose nanofibers substrate, while continuously illuminating the fabricated prototype under ambient condition for an equivalent of 10 years. The unique durability of this flexible substrate will have potential applications in flexible lighting, energy and sensing devices. Graphical abstract: Unlabelled Image Highlights: Pioneering design and fabrication of thermo-stable cellulose nanofibers thin-films up to 190 °C for 5 h of exposure Exceptional design integrity of renewable thin-film for flexible lighting devices with a service life up to 10 years Unique durability model to predict life span for a flexible cellulose nanofiber based electronic device. Novel insight on thermo-oxidative reaction mechanism of cellulose nanofiber.